Testicular Sperm Extraction Techniques in Subfertile Males (Nepalese Medical Journal, 2020)
Introduction: Assisted conception is an option for subfertile couples. Surgical sperm retrieval by testicular sperm aspiration and testicular sperm extraction are widely used safe techniques to yield sperm for intracytoplasmic sperm injection. Experience with these techniques is presented.Materials and Methods: A retrospective study of testicular sperm retrieval for assisted reproduction is presented. Testicular sperm aspiration is attempted on all azoospermic males with normal sexual characteristics. Testicular sperm extraction is attempted on consenting patients where aspiration has failed. Donor sperm injection is done to oocyte of a spouse on the failure of both techniques.Results: Sixty-six percent of males had adequate numbers and characters of viable spermatozoa on testicular sperm aspiration. Further 53.3% of patients where aspiration failed yielded spermatozoa on testicular sperm extraction. Thus overall 77.1 % of patients with azoospermia benefi tted from testicular sperm retrieval techniques.Conclusions: Testicular sperm aspiration is a technically easy, quick, safe, and cheap method of sperm retrieval. Testicular sperm extraction is a safe adjunct to aspiration with better yield.